Sodium iodide symporter, estrogen receptor, and progesterone receptor expression in carcinoma breast - An immunohistochemical analysis - Ashwani Tandon; Ashutosh Shrivastava; Ashok Kumar; Aruna K Prayaga; Challa Sundaram; Madan M Godbole (Wolters Kluwer Medknow Publications, 2011)
Background: Sodium iodide symporter (NIS), a transporter of iodine is essential for thyroid hormone biosynthesis. It also plays a role in the radioiodine treatment of thyroid cancers. NIS mediated radioiodine transport to breast cancers is under active investigation due to its potential therapeutic utility. Cellular localization and quantification using immunohistochemistry may provide clues for its utility in management of carcinoma breast. Materials and Methods: Human NIS (hNIS) expression was therefore assessed by utilizing a rabbit polyclonal antibody raised against a cloned hNIS in different grades of infiltrating duct carcinoma of breast and its metastatic deposits namely in lymph nodes, bone marrow, and endometrium. Further, hNIS expression was compared with prognostic markers namely estrogen receptor (ER) and progesterone receptor (PR). Results: hNIS was positive in 90.6% cases (29/32) and Scarff-Bloom-Richardson grading was done in 25 cases and 23 cases were NIS positive. Among nongraded cases, 2/2 cases of carcinoma in-situ were positive and 4/5 were positive in cases having post therapy residual tumor status. The strong positivity for hNIS was seen irrespective of ER or PR status and of grade of breast carcinoma and correlated well with western blot analysis. In all the three metastatic sites, NIS was positive in the tumor. Conclusion: These findings indicate the utility of immnohistochemistry for NIS as a new potential prognostic marker and may provide guidance for possible radio iodine therapy in breast cancer patients.